Efektifikatas Kombinasi Pupuk Kompos Kubis-Kubisan (Brassicaceae) dan Pupuk Organik Cair Bonggol Pisang terhadap Produksi Kacang Panjang (Vigna Sinensis L.) - Rismawati Harahap; Gusmeizal Gusmeizal; Erwin Pane (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
The purpose of this study was to obtain data on the ability of cabbage compost (Brassicaceae) and banana weevil liquid organic fertilizer on the growth and production of long bean plants (Vigna Sinensis L.). The method used in this study is a randomized block design (RBD) in factorial, with 2 (two) treatment factors, Namely: 1) Factors Cabbage Compost Fertilizer (K); 2) Faktors liquid organic fertilizer banana weevil (P), each treatment was repeated two (2) times so that there are 32 experimental plots. Each experimental plot consisted of 9 plants with 4 plant samples. The parameters were observed in this study consisted of stem diameter, number of pods per sample plant, pod length per sample plant, pod weight per sample plant, production per plot; From the research has been carried out can be concluded as follows: 1) Provision of POC banana weevil has no real effect on stem diameter, number of pods per sample plant, pod length per sample plant, pod weight per sample plant, production per plot; 2) The administration of cabbage compost has a significant effect on stem diameter, number of pods per sample plant and production per plot, but has no real effect on pod length per sample plant and pod weight per sample plant; 3) The combination of the two treatment factors has no real effect on stem diameter, number of pods per sample plant, pod length per sample plant, pod weight per sample plant, production per plot